2018
DOI: 10.1186/s12885-018-4590-4
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs as markers of progression in cervical cancer: a systematic review

Abstract: BackgroundInvasive cervical cancer (ICC) is caused by high-risk human papillomavirus types (HR-HPVs) and is usually preceded by a long phase of intraepithelial neoplasia (CIN). Before invasion, (epi) genetic changes, potentially applicable as molecular markers within cervical screening, occur in HPV host cells. Epigenetic alterations, such as dysregulation of microRNA (miRNA) expression, are frequently observed in ICC. The mechanisms and role of miRNA dysregulation in cervical carcinogenesis are still largely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
120
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(127 citation statements)
references
References 62 publications
1
120
0
6
Order By: Relevance
“…Inflammatory mediators cause dysregulation of miRNAs and vice versa certain miRNAs operate as inflammatory mediators. Dysregulation of miRNAs has been observed during CC development and several dysregulated miRNAs have the ability to modulate the initiation and development of inflammation‐induced cervical carcinogenesis …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammatory mediators cause dysregulation of miRNAs and vice versa certain miRNAs operate as inflammatory mediators. Dysregulation of miRNAs has been observed during CC development and several dysregulated miRNAs have the ability to modulate the initiation and development of inflammation‐induced cervical carcinogenesis …”
Section: Introductionmentioning
confidence: 99%
“…Dysregulation of miRNAs has been observed during CC development and several dysregulated miRNAs have the ability to modulate the initiation and development of inflammation-induced cervical carcinogenesis. 2,22 Exosomes are nanovesicles about 30-150 nm in size and are released by almost all cell types, under both pathological and physiological conditions. These nanovesicles are involved in intercellular communication at both local and systemic levels.…”
Section: Introductionmentioning
confidence: 99%
“…Various screening techniques such as visual inspection with acetic acid (VIA), visual inspection with Lugol's iodine, visual inspection with magnification devices-magnavisualizers, Pap smears cytology, HPV DNA testing have shown efficacy (Table 1). New epigenetic tests are based on either the analysis of the DNA methylation of specific genes [21] or the measurement of the relative expression of microRNAs, which can be easily measured by RT-qPCR-based methods [22]. The applicability, advantages, and drawbacks of different screening tests are summarized in Table 1.…”
Section: Screeningmentioning
confidence: 99%
“…MicroRNAs regulate gene expression mainly through binding to the 3′-untranslated region (UTR) of target mRNAs ( Bartel, 2004 ). As oncogene or tumor suppressor in different cancers, miRNAs play essential roles in basic biological processes such as cell proliferation, apoptosis, differentiation, migration and invasion ( Bartel, 2004 ; Pardini et al, 2018 ). Accumulating studies have shown that miR-29a was abnormally expressed in various cancers, including cervical cancer ( Pei, Lei & Liu, 2016 ; Yang et al, 2017 ; Gong et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%